Different Mechanisms of Four Aluminum (Al)-Resistant Transgenes for Al Toxicity in Arabidopsis - Ezaki, Bunichi (American Society of Plant Physiologists, 2001)
We have characterized the mechanism of action of four transgenes (AtBCB [Arabidopsis blue copper-binding protein], parB [tobacco Nicotiana tabacum glutathione S-transferase], NtPox [tobacco peroxidase], and NtGDI1 [tobacco GDP dissociation inhibitor]) that independently Al resistance on transgenic Arabidopsis. All four transgenic lines showed lower deposition of callose after Al treatment than the Landsberg erecta ecotype of Arabidopsis, confirming that the four genes function to ameliorate Al toxicity. Influx and efflux experiments of Al ions suggested that the AtBCB gene may suppress Al absorption, whereas expression of the NtGDI1 gene promotes a release of Al in the root tip region of Arabidopsis. The total enzyme activities of glutathione S-transferases or peroxidases in transgenic lines carrying either the parB or NtPox genes were significantly higher than in the Landsberg erecta ecotype of Arabidopsis, and these enzyme activities were maintained at higher levels during Al stress. Furthermore, lipid peroxidation caused by Al stress was repressed in these two transgenic lines, suggesting that overexpression of these two genes diminishes oxidative damage caused by Al stress. Al-treated roots of transgenic plants were also stained by 4′,6-diamino-2-phenylindole to monitor cell death caused by Al toxicity. The result suggested that cell death is repressed in the NtPox line. Analysis of F(1) hybrids between the four transgenic lines suggests that more resistant transgenic plants can be constructed by combinations of these four genes.